How Large Was Mars? An investigation of the dimensions of a legendary Swedish warship, 1563–1564. Issue 3 (3rd July 2019) - Eriksson, Niklas
Abstract : The Swedish warship Mars was considered to have been one of the largest ships in the world when it exploded and sank in 1564. The problem is that no written accounts clearly reveal its dimensions. This article reviews how different researchers have discussed the size of Mars in the past. It also aims to shed new light on this topic by using information from the archaeological survey carried out at the wreck site since 2011. Even if the result is approximate it clearly shows that Mars was indeed an impressively large ship by sixteenth century standards, but not as large as many previous researchers have thought.